Strategic Planning for an L2 Program - Rigoberto Castillo (Asociación Colombiana de Profesores de Ingles, 2016)
The article outlines the background and practices that oriented the strategic planning conducted in a language program aimed at different audiences. The plan served as the backbone of professional development to grow with quality at an educational institution, a challenge faced constantly by many programs. The author aims at sharing an experience and at providing insight on how to meet the needs and expectations commonly encountered in managing language programs. The content of this paper hopes to make a contribution on how to build quality from the essence of its operation i.e., the teaching staff.